2018
DOI: 10.1002/da.22721
|View full text |Cite
|
Sign up to set email alerts
|

Will imaging individual raphe nuclei in males with major depressive disorder enhance diagnostic sensitivity and specificity?

Abstract: In agreement with postmortem studies, we found higher 5-HT autoreceptor binding in MDD selectively in the DRN. 5-HT autoreceptor binding in the combined DRN and MRN is a better biomarker for MDD than in the raphe as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(114 reference statements)
2
8
0
Order By: Relevance
“…In contrast, patients with bipolar disorders were found to have higher 5-HT 1A receptor binding using [ 18 F]FCWAY BP p , a measure of binding relative to plasma concentrations of PET tracer ( Nugent et al, 2013a , 2013b ). That finding in bipolar disorder is comparable with our prior work reporting higher 5-HT 1A receptor BP F using [ 11 C]WAY-100635 in patients with current depression or bipolar disorder ( Sullivan et al, 2009 ; Pillai et al, 2018 ; Zanderigo et al, 2018 ), healthy high-risk offspring of parents with mood disorders ( Milak et al, 2018 ), as well as in remitted MDD patients ( Miller et al, 2009 ), suggestive of a biological trait that could confer vulnerability to depression. Some of these discrepancies in terms of the abnormality in depression being high or low binding could be due to discrepancies in PET binding outcome measures (BP ND , BP P , BP F, or BP P /BP F ) and modeling approach for outcome measure estimation, the radioligand used, or the choice of a reference region ( Parsey et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, patients with bipolar disorders were found to have higher 5-HT 1A receptor binding using [ 18 F]FCWAY BP p , a measure of binding relative to plasma concentrations of PET tracer ( Nugent et al, 2013a , 2013b ). That finding in bipolar disorder is comparable with our prior work reporting higher 5-HT 1A receptor BP F using [ 11 C]WAY-100635 in patients with current depression or bipolar disorder ( Sullivan et al, 2009 ; Pillai et al, 2018 ; Zanderigo et al, 2018 ), healthy high-risk offspring of parents with mood disorders ( Milak et al, 2018 ), as well as in remitted MDD patients ( Miller et al, 2009 ), suggestive of a biological trait that could confer vulnerability to depression. Some of these discrepancies in terms of the abnormality in depression being high or low binding could be due to discrepancies in PET binding outcome measures (BP ND , BP P , BP F, or BP P /BP F ) and modeling approach for outcome measure estimation, the radioligand used, or the choice of a reference region ( Parsey et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
“…In a meta-analysis of 10 positron emission tomography (PET) imaging studies, lower 5-HT 1A receptor binding in the mesiotemporal cortex was reported in depressed patients compared with healthy controls ( Wang et al, 2016 ). However, other studies, which were not included in this meta-analysis, found elevated binding in depression during an acute episode and between episodes in remitted patients ( Miller et al, 2009 ; Sullivan et al, 2015 ; Milak et al, 2018 ; Pillai et al, 2018 ). Higher binding was also observed in offspring of parents with major depression and was highest among those who went on to develop depression, indicating that this could be a familial trait ( Milak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 69%
“…Neuroimaging studies with positron emission tomography (PET) have revealed increased binding of the 5-HT1A receptors in the pontine raphe nuclei, both in patients with depression and in patients with migraine. 36 , 37 Moreover, it has been suggested that damage to the raphe nuclei is associated with depressive symptoms in patients who have experienced brainstem strokes. 38 Furthermore, animal studies have implicated a neural circuit involving the dorsal raphe nucleus in depressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Sinogram data were back-projected with filtering onto a 344x344 matrix with scatter correction and no smoothing. Participant motion was corrected by rigid body registration to a reference frame ( Pillai et al, 2018 ) with subsequent coregistration of MRI to the average PET image.…”
Section: Methodsmentioning
confidence: 99%
“…This RN atlas, in MNI space, was created from parametric 5-HT 1A average binding potential maps generated with the 5-HT 1A tracer [ 11 C]-WAY100635. These maps were then thresholded in the midbrain ( Pillai et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%